Large deletions play a minor but essential role in congenital coagulation factor VII and X deficiencies - Rath, M.; Najm, J.; Sirb, H.; Kentouche, K.; Dufke, A.; Pauli, S.; Hackmann, K.; Liehr, T.; Hübner, C. A.; Felbor, U.; Kompetenznetzwerk Hämorrhagische Diathesen Ost (KHDO) (Hämostaseologie, 2015)
Congenital factor VII (FVII) and factor X (FX) deficiencies belong to the group of rare bleeding disorders which may occur in separate or combined forms since both the F7 and F10 genes are located in close proximity on the distal long arm of chromosome 13 (13q34). We here present data of 192 consecutive index cases with FVII and/or FX deficiency. 10 novel and 53 recurrent sequence alterations were identified in the F7 gene and 5 novel as well as 11 recurrent in the F10 gene including one homozygous 4.35 kb deletion within F7 (c.64+430_131–6delins - TCGTAA) and three large heterozygous deletions involving both the F7 and F10 genes. One of the latter proved to be cytogenetically visible as a chromosome 13q34 deletion and associated with agenesis of the corpus callosum and psychomotor retardation.ConclusionsLarge deletions play a minor but essential role in the mutational spectrum of the F7 and F10 genes. Copy number analyses (e. g. MLPA) should be considered if sequencing cannot clarify the underlying reason of an observed coagulopathy. Of note, in cases of combined FVII/FX deficiency, a deletion of the two contiguous genes might be part of a larger chromosomal rearrangement.
Keywords: Factor VII deficiency; factor X deficiency; F7 gene; F10 gene; chromosome 13q34 deletion